Wiping out the covid-19 pandemic through bioinformatics: a review on database and web tools applications - Nur Imaniati Sumantri; Nagisa Eremia Anju; Siti Fauziyah Rahman (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
The COVID-19 is an illness caused by SARS-CoV-2 that has ended up a widespread since March 2020 as declared by WHO. This condition gives a huge impact on miscellaneous sectors enforcing advance use of technology and information system, especially in scientific and medical community. Bioinformatics as a multidisciplinary method plays important role to overcome the COVID-19 outbreak in the early-stage through data exchange in virtual databases. There are a number of free access databases containing basic to complex information of SARS-CoV-2, such as genetic data sequence, epidemiology, evolutionary analysis, pharmacology, and so on. Bioinformatics allows us to analyze the data further to reveal new information applied in biomedical technology activities. Thus, bioinformatics helps the scientists, clinicians, and government learn the genomic characteristics of SARS-CoV-2, to trace the SARS-CoV-2 spread, and select and develop biomarker for reliable diagnostic tools, and design the drug and vaccine for SARS-CoV-2. This review aims to view insights on uses of bioinformatics methods and the databases related to SARS-CoV-2